RESPONSE OF PEARL MILLET TO INTEGRATED USE OF ORGANICS AND FERTILIZERS - N. PRABHU, N. SENTHILKUMAR, P. POONKODI (Journal of Ecobiotechnology, 2018)
In the present study, the integrated organic fertilizers were used to estimate the growth and yield of pearl millet. The treatments consisted of application of increased levels of recommended dose of fertilizer with organic manures for pearl millet. The treatments were; T1-100% RDF,T2-125%RDF,T3-75%RDF, T4-100% RDF + FYM @ 12.5 t ha-1, T5-100% RDF+Poultrymanure@5tha-1,T6-100 % RDF + Vermicompost @ 5 t ha-1, T7-100 % RDF + Pressmud@5tha-1, T8-125% RDF + Poultry manure @ 5 t ha-1, T9-125 % RDF + Vermicompost @ 5 t ha-1, T10-125 % RDF + Pressmud @ 5 t ha-1, T11-75% RDF + Poultry manure @ 5 t ha-1, T12-75 % RDF + Vermicompost @ 5 t ha-1 and T13-75 % RDF + Pressmud @ 5 t ha-1. The experiments were laid out in randomized block design (RBD) and replicated thrice. The result of the experiment revealed that the application of 125% recommended dose of fertilizer + vermicompost@5tha-1(T9), significantly increased the growth, yield, quality and nutrient uptake of pearl millet followed by, T10 (125% recommended dose of fertilizer + Pressmud @ 5 t ha-1) respectively.